Analytical challenges when sampling and characterising exhaled aerosol - Gregson, Florence K. A.; Sheikh, Sadiyah; Archer, Justice; Symons, Henry E.; Walker, Jim S.; Haddrell, Allen E.; Orton, Christopher M.; Hamilton, Fergus W.; Brown, Jules M.; Bzdek, Bryan R.; Reid, Jonathan P. (Aerosol science and technology, 2022)
Respiratory particles produced by breathing, coughing, and speaking or generated during medical procedures serve as important routes for disease transmission. Characterizing the number of particles generated as well as their size distribution is fundamental for guiding policy on infection control. However, sampling such particles carries inherent challenges. Respiratory particles are polydisperse in size, temporally and spatially variable, and emitted in very low concentrations, usually lower than the preexisting aerosol concentration in indoor environments. In addition, they are typically emitted in a highly dynamic, warm and humid jet, leading to further rapid processes, such as dispersion and evaporation. Here, we discuss important considerations for sampling respiratory aerosol, focusing on sampling particles <20 μm in diameter. Instruments capable of counting single-particles within this size range are commercially available. We provide recommendations for experimental protocols and demonstrate the limitations behind such approaches. We highlight the importance of a measurement space with as low a background aerosol concentration as possible, and of sampling for as long as possible to enable accurate quantitation of the size distribution of an aerosol plume. This is particularly important for the larger particles (>5 μm diameter) that are so low in concentration that they may require hours of sampling time to be accurately quantified. We explore the relationship between the flow rates of the exhalation and the sampling instrument and the consequent quantification of particle flux. We also discuss the transport and evaporation dynamics of liquid particles within respiratory jets, and their impacts on conducting aerosol sampling studies.